Cover Picture: A Metallaanthracene and Derived Metallaanthraquinone (Angew. Chem. Int. Ed. 1/2017). Issue 1 (22nd November 2016) - Frogley, Benjamin J.; Wright, L. James
Abstract : Unlike metallabenzenes, which are well known metalla‐analogues of linear polycyclic hydrocarbons, are currently restricted to a few metallanaphthalenes. In their Communication onpage 147 ff., L. J. Wright and B. J. Frogley describe an extension of these compounds to the first metallaanthracene, which serves as a precursor for other new metallaarenes. In the picture (in which iridium and its ancillary ligands are the eyes), cartoonist Nick Kim depicts the "evolution" of polycyclic metallaarenes with ultimate formation of an iridaanthraquinone "daughter".